-5(x-8)=-4(x+7)

Simple and best practice solution for -5(x-8)=-4(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-8)=-4(x+7) equation:


Simplifying
-5(x + -8) = -4(x + 7)

Reorder the terms:
-5(-8 + x) = -4(x + 7)
(-8 * -5 + x * -5) = -4(x + 7)
(40 + -5x) = -4(x + 7)

Reorder the terms:
40 + -5x = -4(7 + x)
40 + -5x = (7 * -4 + x * -4)
40 + -5x = (-28 + -4x)

Solving
40 + -5x = -28 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
40 + -5x + 4x = -28 + -4x + 4x

Combine like terms: -5x + 4x = -1x
40 + -1x = -28 + -4x + 4x

Combine like terms: -4x + 4x = 0
40 + -1x = -28 + 0
40 + -1x = -28

Add '-40' to each side of the equation.
40 + -40 + -1x = -28 + -40

Combine like terms: 40 + -40 = 0
0 + -1x = -28 + -40
-1x = -28 + -40

Combine like terms: -28 + -40 = -68
-1x = -68

Divide each side by '-1'.
x = 68

Simplifying
x = 68

See similar equations:

| 12x+6=6+12x | | 3.5a=14 | | 6-(-6)=x | | -3x+18=7x-2 | | 3y-3+4y=7 | | 6-(-18)=x | | 2x^2+-x+-3=0 | | m+7=22 | | 6+(-18)=x | | 16x^2+8xy+y^2= | | y=-3x+18 | | 28=4y-6 | | 2m+7=22 | | (6x-2)=56 | | A-3.5=14 | | 5x^2+17x+-12=0 | | e^6x=13 | | 9(-4x+2)=7x | | 2x+30=-2x+2 | | 5x+3y=-29 | | e^3x=13 | | 6x^2+11x+-2=0 | | 5-(-7)=12 | | 5(w+12)= | | 4x-5+3x=9 | | 4q=7q+37 | | 1.5-0.25(a+4)=3+(.05-0.5a) | | 4t^2+18t-400=0 | | -20=-7x+1 | | 5(-4x-3)=13x+9 | | -50-7x=-3x+62 | | 312x+51=33 |

Equations solver categories